Molecular markers associated with the agronomic traits in the medicinal plant lemon balm - Sanam Safaei-Chaeikar; Mehdi Rahimi (Acta Scientiarum. Biological Sciences, 2017)
Finding association between molecular markers and agronomic traits provide an excellent tool for indirect selection of a trait of interest in the population. In this study, stepwise regression analysis was used to estimate associations between ISSR and RAPD markers with some agronomic traits in lemon balm ecotypes. The analysis of results revealed significant associations between the traits and some of the studied loci. For all the traits, more than one informative marker was detected. Totally,90informative markers, including 48 ISSR loci and 42 RAPD loci, were identified. The SA-R-10, UBC826-1, UBC812-9, UBC813-10, UBC825-4, OPA-01-15, OPC-04-7 and CS-56-8 markers or fragment showed a significant correlation with Essential oil percentage and controlled 99.8% of the phenotypic variation. These markers are relatively more reliable. Among the RAPD primers, special attention should be drawn to primer SA-R, which had the highest associated fragments with the traits including days for 50% flowering, number of branches per plant, fresh weight and dry weight. Some of ISSR and RAPD markers were associated with more than one trait in multiple regression analysis that may be due to pleiotropic effect of the linked quantitative trait locus on different traits or its linkage to different genes. These primers have been found useful for improved lemon balm.